Women and Epistemic Injustice:An Ideological Critique of Genesis 16:1-16 from a Feminist Perspective - Lely Irene Mussa; Wanta Khosin (Program Pascasarjana UKIM, 2025)
The act of epistemic injustice against women in the present is exacerbated by theological discourse, which suggests that God approves of such injustice. The core of epistemic injustice against women lies in the denial of opportunities to women in any form. The narrative of Genesis 16:1-16 illustrates this reality, with Hagar (an Egyptian) as a slave fleeing from the injustice inflicted upon her. In this narrative, God and Abraham are depicted as passive figures who legalize injustice. Affirming this reality, the author intends to interpret the narrative of Genesis 16:1-16 using ideological critique developed by Jeffrey Fager and feminist perspectives. The author also compares it with the contemporary context of epistemic injustice as an inseparable part of theologizing. The interpretation process employs ideological critique and feminist perspectives. This research focuses on advocating for justice by listening to and seeing marginalized and oppressed people. The ignored voices of women are given space to provide testimony within the text.